1994
DOI: 10.1084/jem.180.5.1805
|View full text |Cite
|
Sign up to set email alerts
|

Light chain editing in kappa-deficient animals: a potential mechanism of B cell tolerance.

Abstract: SummaryThe genetic organization of the g and X light chain loci permits multiple, successive rearrangement attempts at each allele. Multiple rearrangements allow autoreactive B cells to escape clonal deletion by editing their surface receptors. Editing may also facilitate efficient B cell production by salvaging cells with nonproductive light chain (L chain) rearrangements. To study receptor editing of g L chains, we have characterized B cells from mice hemizygous for the targeted inactivation of g (JCkD/wt) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
83
2

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(89 citation statements)
references
References 60 publications
4
83
2
Order By: Relevance
“…Also consistent with this idea is the observation that in 3-83KI mice bred to signaling mutants that result in increased sIg levels, receptor editing is blocked (V.K., unpublished results). Analysis of B cell tumor lines and B cells of Ig-Tg mice has indicated that multiple rearrangements can occur on individual Igloci and that these might be induced spontaneously (13,28,29), because initial VJ joins were out of frame (30), because of an inability to pair with H chain (31), or because of immune tolerance (9,10,21,32,33). In addition, the inability of certain Ig-transgenes to mediate feedback suppression of Ig gene rearrangements has sometimes been ascribed to insufficient gene expression (34,35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also consistent with this idea is the observation that in 3-83KI mice bred to signaling mutants that result in increased sIg levels, receptor editing is blocked (V.K., unpublished results). Analysis of B cell tumor lines and B cells of Ig-Tg mice has indicated that multiple rearrangements can occur on individual Igloci and that these might be induced spontaneously (13,28,29), because initial VJ joins were out of frame (30), because of an inability to pair with H chain (31), or because of immune tolerance (9,10,21,32,33). In addition, the inability of certain Ig-transgenes to mediate feedback suppression of Ig gene rearrangements has sometimes been ascribed to insufficient gene expression (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…At this developmental stage, surface Ig (sIg) binding to self-antigens leads to developmental block and elimination of autoreactive B cells by cell death, or to alteration of antibody specificity by receptor editing (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). When appropriate IgM appears on the surface of developing B cells, further maturation follows, but expression of a nonautoreactive Ig-H͞ L-chain complex may be insufficient to promote B cell maturation (11).…”
mentioning
confidence: 99%
“…Expression of Ig κ and λ L chain was determined by a sandwich ELISA using goat anti-mouse Ig κ and goat antimouse Ig λ antibody (Southern Biotechnology). Vκ use in 56R H-chain-containing hybrids was analyzed by PCR using primers listed in Table S3 as described previously (15,17,(44)(45)(46)(47)(48).…”
Section: Methodsmentioning
confidence: 99%
“…Shown for comparison are previously published data from hybridoma panels from 3H9.κ-/κ-, 56R.κ-/κ-, and nontg κ-/κ-mice (13; data from ref. 60, copyright 1994, Rockefeller University Press). κ-/κ-refers to homozygous κ-deficiency.…”
Section: Hybridomasmentioning
confidence: 99%